THE IMPACT OF ENTREPRENEURIAL TRAINING PROGRAM ON ENTREPRENEURIAL INNOVATIVENESS: A CASE STUDY AMONG START-UP ENTREPRENEURS IN PITCHBORNEO - Saverinus P. Kitingan (Malaysian Journal of Business and Economics (MJBE), 2020)
This study presents an examination of the impact of the Pitchborneo training program as an entrepreneurial program focused on entrepreneurial innovativeness for idea generation, development and presentation (the pitch) among start-up entrepreneurs in Sabah, Malaysia. Pitchborneo is a unique entrepreneurial training program which is also a disbursement vehicle of government grant worth RM200,000 annually since 2011. In this study, the objectives are: (i) to determine the level of effectiveness of the Pitchborneo training program based on content, delivery, mentoring and coaching, and training needs fulfilment; (ii) to determine the level of entrepreneurial innovativeness in terms of idea generation, development and presentation; (iii) to compare entrepreneurial innovativeness of the start-up entrepreneurs based on their demographics (age, gender, highest academic qualification, length of business experience); and (iv) to determine the impact of the Pitchborneo training program on the entrepreneurial innovativeness of the start-up entrepreneurs. This descriptive and quantitative study used online survey to gather information from 200 respondents who were randomly selected from past participants of Pitchborneo program. Descriptive and inferential statistical analyses using IBM SPSS 23.0 determines the level of training effectiveness and innovativeness in idea generation, development and presentation, as well as to test the research hypotheses. Findings showed that respondents perceived highly of the Pitchborneo training program in terms of content, delivery, coaching and mentoring, and fulfilment of training needs. It was also found that entrepreneurial innovativeness was high and not differentiated by demographics. The Pitchborneo training program impacted significantly on entrepreneurial innovativeness. For future research, it is recommended to focus on pitching competencies among the entrepreneurs. This study concludes the effectiveness of Pitchborneo and its potential as a model of best practice and benchmarking to other organizations offering entrepreneurship education.